Sekundární pyomyozitida kyčelních svalů (nontropical pyomyositis) - Koudela, Karel; Koudela, Karel; Koudelová, Jana; Kunešová, Martina (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2008)
By presenting the results of treatment of secondary pyomyositis of deep hip muscles, to draw attention to the seriousness of this complication occurring in association with pelvic and lumbo-sacral infections. MATERIAL AND METHODS: The course of disease was evaluated retrospectively in a group of 13 patients with an average age of 65.8 years treated in the period from April 2004 to June 2007. The imaging methods used included native radiography, ultrasonography (SONO), computed tomography (CT) and magnetic resonance imaging (MRI). Markers of inflammation, i.e., C-creative protein, erythrocyte sedimentation rate and WBC differential count, were used to assess the intensity of inflammation. At stage 1, patients were treated conservatively, with appropriate antibiotic therapy. At stages 2 and 3, surgical procedures were used (incision, abscess evacuation and drainage) or abscess was treated by CT-guided needle puncture and pigtail drain insertion. The evaluation took into account survival of the patients in relation to the stage of their disease, early detection of origin of infection, therapy initiation, and other factors putting patients at risk. RESULTS: Of the 13 patients treated, 10 had stage 3 pyomyositis with beginning or developed multiple-organ failure when they were referred to our institution from outside hospitals; three admitted at stage 2 pyomyositis were in relatively good state. Ten patients were cured, two died due to multiple-organ failure and one due to pulmonary embolism after lower-extremity phlebothrombosis. The success of treatment appeared to be related to early surgical intervention. DISCUSSION: A good outcome of therapy depends on an early diagnosis and treatment of the underlying infection and pyomyositis. To establish the diagnosis of pyomyositis, repeated clinical, laboratory and bacteriological examinations are necessary, as well as the use of imaging methods, namely SONO, CT and MRI. Treatment may be complicated when small multiple abscesses develop deep in the hip muscles where surgical intervention is difficult. CONCLUSIONS: Secondary pyomyositis is a serious, life-threatening complication of the underlying infection. The outcome of the disease depends on early diagnosis, therapy and the patient's overall state. Stage 1 pyomyositis (muscle oedema) is treated conservatively with antibiotics. Stage 2 pyomyositis needs surgical intervention with abscess aspiration and drainage; in some cases CT-guided needle puncture with pigtail drain insertion is sufficient. An appropriate antibiotic course is obligatory. Stage 3 pyomyositis associated with septic shock or multiple-organ failure requires a comprehensive care in an acute medicine department. In polymorbid patients prognosis is poor and treatment is expensive and often unsuccessful.
Keywords: absces; senioři; kyčel; pyomyozitida; Tomography, X-Ray Computed; Pyomyositis; Middle Aged; mužské pohlaví; magnetická rezonanční tomografie; Magnetic Resonance Imaging; ženské pohlaví; Humans; Hip; lidé středního věku; Abscess; počítačová rentgenová tomografie; Aged; Female; lidé; Male